1990
DOI: 10.1530/jrf.0.0900011
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E-2 as a potential luteotrophic agent during early pregnancy in cattle

Abstract: Summary. Heifers slaughtered on Day 18/19 of pregnancy had significantly higher (P < 0\m=.\001) concentrations of PGE-2 (measured as its methyl oxime) in uterine flushings than did animals slaughtered on Days 6 or 12 of pregnancy, or on Days 6 or 12 of the oestrous cycle. In addition, concentrations were higher in the uterine horn ipsilateral to the corpus lueum on Days 12 (P < 0\m=.\05) and 18/19 (P < 0\ m=. \ 01) than in the contralateral horn. Incubation of dispersed luteal cells for 3 h with LH (0\ m=. \ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
4
19
1
Order By: Relevance
“…Our results are consistent with other studies in utero, as the total amount of PGs were over three times higher in Day 13 pregnant after multiple ET than in cyclic heifers (Spencer et al, 2013). In particular, concentrations of PGF 2 α normally exceed several times that of PGE 2 (Bartol et al, 1981;Lewis et al, 1982;Shelton et al, 1990;Ulbrich et al, 2009). At such stages, PGs activate a number of IFNT-stimulated genes, and it seems that PGs could be important recognition signalling molecules in cattle (Spencer et al, 2013;Lonergan and Forde, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with other studies in utero, as the total amount of PGs were over three times higher in Day 13 pregnant after multiple ET than in cyclic heifers (Spencer et al, 2013). In particular, concentrations of PGF 2 α normally exceed several times that of PGE 2 (Bartol et al, 1981;Lewis et al, 1982;Shelton et al, 1990;Ulbrich et al, 2009). At such stages, PGs activate a number of IFNT-stimulated genes, and it seems that PGs could be important recognition signalling molecules in cattle (Spencer et al, 2013;Lonergan and Forde, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Different superscript letters indicate significant differences between groups (P!0.05). Bartol et al 1981, Lewis et al 1982, Shelton et al 1990. Highest levels of PGF 2a and PGE 2 opposed to low levels of PGD 2 , TXB 2 , and 6-keto PGF 1a were found in ovine luminal cell supernatants treated with [ 3 H]AA, whereby the latter authors specifically point out that exogenous [ 3 H]AA may not reflect endogenous synthesis capabilities (Charpigny et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…PG released from the endometrium not only reach blood vessels, but also appear in the uterine lumen. Early studies have demonstrated PGF 2a and PGE 2 in in vivo flushings (Ellinwood et al 1979, Bartol et al 1981, Shelton et al 1990. Additionally, the conversion Figure 3 The concentrations of the prostaglandins and metabolites vary with respect to day and status in uterine flushings.…”
Section: Discussionmentioning
confidence: 99%
“…The production of prostaglandin F2 (PGF2) is responsible for luteolysis and prostaglandin E 2 (PGE 2 ) is involved in maternal recognition of pregnancy (Arosh et al 2002;Shelton et al 1990) and as such these pathways are of major importance in early embryonic development. Triglycerides are not only important in membrane synthesis but are also suggested to have a role in early embryonic development as an energy source (Ferguson and Leese 2006;Forde et al 2009a).…”
Section: Discussionmentioning
confidence: 99%